2016
DOI: 10.1002/cam4.619
|View full text |Cite
|
Sign up to set email alerts
|

Role of palliative radiotherapy in the management of mural cardiac metastases: who, when and how to treat? A case series of 10 patients

Abstract: Cardiac metastases (CM), although a rare manifestation of metastatic cancer, are increasing in incidence with the improved prognosis and increased longevity of many patients with cancer. This condition may be life‐threatening, especially for bulky rapidly growing tumors. Such cancer presentations may be amenable to palliative radiotherapy to improve symptoms and to prevent further cardiac function decline. Here, we report on our experience with 10 patients with mural CM who received radiotherapy (RT) to the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…In our case, we assume that the CHB was persistent after trying to correct possible external causes, such as hypercalcemia and hypokalemia, and after a sufficient waiting period. Moreover, it is still also unknown whether CHB would resolve after cancer treatment 2,20 . Our literature review showed that there are only two cases of metastatic CHB that are reversible after undergoing chemotherapy for cardiac metastasis 8,12 , while several other cases showed that CHB is irreversible [2][3][4][5][6][7][9][10][11][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we assume that the CHB was persistent after trying to correct possible external causes, such as hypercalcemia and hypokalemia, and after a sufficient waiting period. Moreover, it is still also unknown whether CHB would resolve after cancer treatment 2,20 . Our literature review showed that there are only two cases of metastatic CHB that are reversible after undergoing chemotherapy for cardiac metastasis 8,12 , while several other cases showed that CHB is irreversible [2][3][4][5][6][7][9][10][11][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we assume that the CHB was persistent after trying to correct possible external causes, such as hypercalcemia and hypokalemia, and after a sufficient waiting period. Moreover, it is still also unknown whether CHB would resolve after cancer treatment 2,20 . Our literature review showed that there are only two cases of metastatic CHB that are reversible after undergoing chemotherapy for cardiac metastasis 8,12 , while several other cases showed that CHB is irreversible [2][3][4][5][6][7][9][10][11][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent trials of programmed death receptor-1 (PD-1)/PD-L1 inhibitors have demonstrated durable responses with long-term survival, and five immune checkpoint inhibitors have received FDA approval in this disease, including atezolizumab [ 7 - 10 ]. Radiation has rarely been used with success in the treatment of cardiac metastases, and only a limited number of successfully treated cases and techniques have been documented [ 2 , 4 - 5 ]. Additionally, radiotherapy increases the presentation of antigens to immune cells, potentially enhancing T-cell killing of tumor cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac metastases almost always indicate systemic disease and are seldom a solitary event [ 1 - 2 ]. Management is generally directed toward symptom control and maintaining cardiac function; however, long-term survival is rare, with a median survival around 3.5 months without treatment [ 1 , 3 - 4 ]. Here, we report a case of isolated metastatic urothelial cell carcinoma to the right ventricle.…”
Section: Introductionmentioning
confidence: 99%